2011
DOI: 10.1080/09593330.2010.501821
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of molecular weight distribution for the liquid fraction of pig slurry treated by anaerobic digestion

Abstract: Pig slurry was treated in an upflow anaerobic sludge blanket (UASB) reactor. To maintain a stable operation, the organic loading rate (OLR) applied to the system was increased stepwise by decreasing the dilution ratio of the pig slurry. Finally, during the last operational stage, no dilution was applied to the influent. The reactor maintained a soluble chemical oxygen demand (CODs) removal efficiency of 82% when OLRs lower than 1.73 g CODs l(-1) d(-1) were applied, although its efficiency fell to 55% when oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…A number of technologies are being used for waste water treatment; whereby anaerobic digestion (AD) is relatively cost effective technology [1][2][3]. AD is a complex process with several advantages over the con ventional aerobic technologies, such as no require ment for aeration, high productivity of biogas and low yield of sludge.…”
mentioning
confidence: 99%
“…A number of technologies are being used for waste water treatment; whereby anaerobic digestion (AD) is relatively cost effective technology [1][2][3]. AD is a complex process with several advantages over the con ventional aerobic technologies, such as no require ment for aeration, high productivity of biogas and low yield of sludge.…”
mentioning
confidence: 99%
“…Although adapted biomass can support free ammonia concentrations up to 3 g NH3-N/L (Guerrero et al 1997;Nielsen and Angelidaki, 2008;González-Fernández and García-Encina, 2009). Furthermore, Rodríguez et al (2011) observed a very good performance of the anaerobic continuous system under concentration of ammonia higher than 375 mg NH3-N/L.…”
Section: Rw and Tw Characterizationmentioning
confidence: 90%
“…The animals' physiological state and diet as well as the buildings and waste management period result in different physical-chemical characteristics ). In general, swine wastewater characterization shows high organic matter (4.2-12.3 g BOD 5 /L), electric conductivity (5150-8425 µS/cm), solids (total: 12.6-53.9 g/L; volatile: 7.8-21.7 g/L), fecal coliforms (4.2 x 10 7 -1.9 x 10 8 MPN 100/mL) and nutrients (4.8-720 mg/L of total nitrogen, 486-954 mg NH 4 + -N/L, 266-1600 mg P/L) (Teira-Esmatges and Flotats 2003; Ahn et al 2004;Boursier et al 2005;Vanotti, et al 2007;González-Fernández et al 2008a;Rodríguez et al 2011). In addition to heavy metals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During Phase II (1.1 g L -1 d -1 of COD), organic matter removal efficiency and transfer to the gaseous phase of part of ammonium were, on average, 70 % and 25 %, respectively. Sánchez et al (2005) and Rodríguez et al (2011) During Phases I and II, the alkalinity ratio decreased from 0.5 to 0.3 and pH increased from 7.1 to 8.1. This is also related to partial alkalinity increasing from 2 to 5 times in the effluent.…”
Section: Relationship Between Odor Generation and Biogas Production: mentioning
confidence: 99%
“…UASB systems are anaerobic treatment technologies used in this field, which exhibit optimal removal of organic matter and proteins (over 75 % and close to 80 %, respectively) at temperatures between 30 and 35 °C, pH close to 7 and OLR below 1.8 g L -1 d -1 of COD. These conditions are related to biogas production (over 0.2 L g -1 VS added of CH 4 or about 0.1 L g -1 protein added of CH 4 ) (Sánchez et al, 2005;Chae et al, 2008;Rodríguez et al, 2011), and decrease of VFA (over 60 %) (Sánchez et al, 2005) and ammonium (about 30 %) (Belmonte et al, 2011). Therefore, the aim of this study was to evaluate the influence of pH, temperature and organic loading on the odor from anaerobic digestion of swine slurry.…”
Section: Introductionmentioning
confidence: 99%